(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Purpose: The purpose of this study was to assess impacted mandibular 3rd molar radiologically in 33 Bangladeshi patients. Methodology: Radiographic evaluation (by orthopantomogram) of 53 impacted mandibular 3rd molar teeth of 33 Bangladeshi patients of ages ranged from 21 to 70 years was done who were conveniently selected from patients attended to department of Oral & Maxillofacial Surgery, Dhaka dental College Hospital & Confidence Dental Surgery, Dhaka. Result: In the study of 33 patients, 21 (63.64%) were males and 12 (36.36%) were females. Out of 53 impacted teeth of 33 patients, highest number of mandibular third molars were in vertically position (39 teeth, i.e. 73.59%), followed by horizontal (8 teeth, i.e. 15.09%), mesio-angular (4 teeth, i.e. 7.54%), and disto-angular (1 tooth, i.e. 1.87%) position. Maximum number of third molars were at level A (29 teeth, i.e., 54.71%), followed by level B (18 teeth, i.e., 33.97%) and level C (06 teeth, i.e., 11.32%). 43 mandibular third molars were in class II relation (81.12%), followed by 8 teeth (15.09%) in class I relation and 2 teeth (3.78%) in class III relation. Conclusion: The pattern of Impaction of mandibular 3rd molar is characterized by high prevalence in male. The most common type is vertical, the most common position is position A and the most common class is Class-II. J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 36-39